Implementasi Kurikulum 2013 Perubahan pada Mata Pelajaran Sejarah di SMA Negeri 1 Seputih Raman - Setio Handayani; Muhammad Basri; Yustina Sri Ekwandari (FKIP UNIVERSITAS LAMPUNG, 2018)
The purpose of the study was to describe the implementation of the 2013 Curriculum Changes on History Subject at Senior High School 1 Seputih Raman for even semester 2017/2018 Academic Year. This study applied a qualitative descriptive field research. The data collecting technique was conducted through observation, interviews, and documentation. The data analysis was carried out using triangulation techniques. Based on the data analysis carried out using Ali formula, the results showed that the readiness of teachers in implementig the 2013 Curriculum Changes on History Subject at SHS 1 Seputih Raman related to the overall planning of learning process, the percentage of teachers' readiness was 74.17%, which classified in the